Adherence to breast cancer screening protocols in the female teaching staff of the San Gregorio de Portoviejo University - Alarcón, Daniel; Alarcón, Ana; Almeida, Brenda; Mendoza, Micaela; Zambrano, Nashly (Revista Gregoriana de Ciencias de la Salud, 2024)
Breast cancer constitutes a public health problem; it is necessary to have adequate prevention and follow screening protocols to have an early diagnosis and improve the prognosis of the pathology. The objective of this work was to determine adherence to breast cancer screening protocols in the female teaching staff of the San Gregorio de Portoviejo University. An exploratory cross-sectional study was carried out. An original survey was developed, anonymously, with the participation of 61 teachers from the institution. 63% of the surveyed population does have knowledge about breast cancer screening protocols, 84% perform breast self-examination. 44% of women over 40 years of age do not undergo mammography, with 81% expressing lack of time as the main reason. It is necessary to improve adherence to screening protocols to make significant progress in reducing the incidence and mortality from breast cancer.